2018
DOI: 10.1158/0008-5472.can-17-2325
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Cyclin D-CDK4/6 Sensitizes Immune-Refractory Cancer by Blocking the SCP3–NANOG Axis

Abstract: Immunoediting caused by antitumor immunity drives tumor cells to acquire refractory phenotypes. We demonstrated previously that tumor antigen-specific T cells edit these cells such that they become resistant to CTL killing and enrich NANOG cancer stem cell-like cells. In this study, we show that synaptonemal complex protein 3 (SCP3), a member of the Cor1 family, is overexpressed in immunoedited cells and upregulates NANOG by hyperactivating the cyclin D1-CDK4/6 axis. The SCP3-cyclin D1-CDK4/6 axis was preserve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 45 publications
(78 reference statements)
0
42
0
Order By: Relevance
“…Oh and colleagues studied a highly immune-refractory cancer and found that synaptonemal complex protein 3 (SCP3) is overexpressed in immune-edited cancer cells and upregulates the pluripotency transcriptional factor NANOG by hyperactivation of the Cyclin D-CDK4/6 axis. In this model, the combination of palbociclib together with adoptive cytotoxic cell transfer showed considerable therapeutic efficacy, suggesting a niche role for CDK4/6 inhibitors in immunotherapy combinations in the resistant/refractory setting (79).…”
Section: Effects On Pd-l1 and Other Coinhibitor Molecule Expressionmentioning
confidence: 87%
“…Oh and colleagues studied a highly immune-refractory cancer and found that synaptonemal complex protein 3 (SCP3) is overexpressed in immune-edited cancer cells and upregulates the pluripotency transcriptional factor NANOG by hyperactivation of the Cyclin D-CDK4/6 axis. In this model, the combination of palbociclib together with adoptive cytotoxic cell transfer showed considerable therapeutic efficacy, suggesting a niche role for CDK4/6 inhibitors in immunotherapy combinations in the resistant/refractory setting (79).…”
Section: Effects On Pd-l1 and Other Coinhibitor Molecule Expressionmentioning
confidence: 87%
“…3, B and C), indicating an important role of CXCL10 in the property mediated by TCTP. For the TCTP-mediated anti-apoptotic response to CTLs, we noted an increase in anti-apoptotic protein MCL-1, a signature molecule rendering tumor cells resistant to CTLinduced killing in previous studies 12,14,19 , in CT26 P3 cells as well as CT26 TCTP cells, relative to P0 or CT26-no cells, respectively (Supplemental Fig. 5C and Fig.…”
Section: Tctp Is Required For Immune-refractoriness To Anti-pd-l1 Thementioning
confidence: 57%
“…Accumulating evidence has demonstrated that consistent and evolving reciprocal interaction between the anti-cancer immune system and tumor cells confers intrinsic-and/or extrinsic-resistance to immunotherapy. In the immunoediting process, CTL-mediated immune selection drives the adaptation of tumor cells to host immune surveillance, thereby contributing to generating tumor cells with intrinsicresistance to CTL attack 12,14 . Conversely, tumor cells repress anti-tumor immunity through impairing TIL recruitment to the tumor and effector function, known as extrinsic-resistance 15,17,55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations